2011
DOI: 10.1017/s1368980011002242
|View full text |Cite
|
Sign up to set email alerts
|

Who is missing the message? Targeting strategies to increase food label use among US adults

Abstract: Objective: To evaluate the associations between sociodemographic and psychosocial characteristics and food label (FL) use in US adults. Design: Data from the 1994-1996 Continuing Survey of Food Intakes by Individuals and the Diet and Health Knowledge Survey were used. High socio-economic status (SES) was defined as .high school education and poverty-income ratio (PIR) .350 %, low SES as ,high school level or PIR ,130 %. Dietary intakes were assessed using 24 h recalls. Setting: Metropolitan statistical area-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
23
6
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 26 publications
12
23
6
2
Order By: Relevance
“…However, with males in Australia and New Zealand accessing health services at lower levels than females (43,44) , use of other community settings or workplace initiatives to provide factual information about the Tick (and other 'better for you' labelling schemes) may be most effective in promoting their use and helping men to choose healthier foods (45) . In our study, 40 % of participants reported living in rural areas and our finding of greater use of the Tick by women living in these areas contrasts with a recent study of US adults which found food label use less likely in rural dwellers (11) . Our finding may reflect regional lifestyle and health differences in Australia, where women in rural areas may be more often the primary household food shopper, or have higher rates of hypertension (and better nutrition awareness and food label use) (12) , compared with women living in urban areas (46) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, with males in Australia and New Zealand accessing health services at lower levels than females (43,44) , use of other community settings or workplace initiatives to provide factual information about the Tick (and other 'better for you' labelling schemes) may be most effective in promoting their use and helping men to choose healthier foods (45) . In our study, 40 % of participants reported living in rural areas and our finding of greater use of the Tick by women living in these areas contrasts with a recent study of US adults which found food label use less likely in rural dwellers (11) . Our finding may reflect regional lifestyle and health differences in Australia, where women in rural areas may be more often the primary household food shopper, or have higher rates of hypertension (and better nutrition awareness and food label use) (12) , compared with women living in urban areas (46) .…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have also found that people with unhealthy diets are less likely (than those with healthier diets) to be influenced by food labels when making decisions about which food products they will purchase (5)(6)(7)(8) . Consumers who use food labels and nutrition information on food packaging are more likely to be highly educated, nutritionally knowledgeable (9)(10)(11)(12) , female, older, with a healthy weight and/or weight conscious (13)(14)(15) , diagnosed with a chronic disease (12,(14)(15)(16) , acknowledge the diet-disease relationship, have accurate self-perception of body weight and live in urban areas (11) . A major challenge of promoting use of nutrition labels and claims is ensuring that consumers understand the label and that it does, indeed, assist them in making appropriate food choices (17) .…”
mentioning
confidence: 99%
“…These findings were broadly consistent with previous research indicating that comprehension of nutrition labels-and health literacy, more generally-is lower among more disadvantaged individuals and older individuals. 4,5,9,14,15 The findings on ethnicity, similar to previous studies using the NVS tool, indicate lower health literacy among minority groups. 14,15 As with research conducted by Shah et al, 15 BMI was not significantly associated with health literacy in the current study.…”
Section: Discussionsupporting
confidence: 81%
“…8 Despite widespread use and high levels of confidence among Canadians, there is evidence that many have difficulty understanding and applying the nutrition information. 4,6,9 Difficulties with serving sizes and converting nutrient amounts are particularly apparent in older adults and people with lower education and income. [4][5][6] Thus, although Canadians consider themselves knowledgeable with respect to labels, they may not fully understand how many calories they have consumed based on serving size information.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the prevention and management strategy of obesity should be to reinforce consumers' perception and use of nutrition labeling of foods [8]. Previous studies have investigated the predictors, strategies, impacts, and effectiveness on nutrition label use [7,8,[11][12][13][14][15][16][17][18][19][20][21]. Studies on the factors associating nutrition labeling and obesity are limited.…”
Section: Introductionmentioning
confidence: 99%